2013
DOI: 10.1016/s0924-9338(13)76454-x
|View full text |Cite
|
Sign up to set email alerts
|

1419 – Language changes as an important psychopathological phenomenon of mild depression

Abstract: ObjectiveDifficulties in diagnostics of mild depressions are related to clinical interpretation of thought structure and content within depressive triad. Whereas nonverbal (motor) and affective components are similar to variations of normal sadness in healthy individuals, associative component reveals the most sensitive psychopathological finding being represented in definite language changes.Methods124 patients and 77 healthy controls, including 35 with normal sadness reactions, were observed. Speech (superfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An examination of essays written by depressed, formerly-depressed, and non-depressed college students at University of Texas [17] confirmed an elevated use of the word "I" in particular and also found more negative emotion words in the depressed group. Similarly, a Russian speech study [18] found a more frequent use of all pronouns and verbs in past tense among depression patients. A recent study based on English forum posts [19] observed an elevated use of absolutist words (e.g., absolutely, completely, every, nothing 1 ) within forums related to depression, anxiety, and suicidal ideation than within completely unrelated forums as well as ones about asthma, diabetes, or cancer.…”
Section: Depression and Languagementioning
confidence: 79%
See 1 more Smart Citation
“…An examination of essays written by depressed, formerly-depressed, and non-depressed college students at University of Texas [17] confirmed an elevated use of the word "I" in particular and also found more negative emotion words in the depressed group. Similarly, a Russian speech study [18] found a more frequent use of all pronouns and verbs in past tense among depression patients. A recent study based on English forum posts [19] observed an elevated use of absolutist words (e.g., absolutely, completely, every, nothing 1 ) within forums related to depression, anxiety, and suicidal ideation than within completely unrelated forums as well as ones about asthma, diabetes, or cancer.…”
Section: Depression and Languagementioning
confidence: 79%
“…The resulting tokens of each message were lowercased (with the exception of emoticons) and separated with a space to enable fastText to properly treat punctuation. 17 Since the dataset also contains messages written in different languages than English and a sophisticated language detection classifier would have required too much time for so many documents, a simple language detection based on stopword counts was utilized: Only messages with more English stopwords than ones from other languages 18 were retained (thus also discarding messages without any stopwords). This resulted in a final training corpus of 1.37 billion messages and a total of 49.9 billion tokens.…”
Section: Word Embeddingsmentioning
confidence: 99%
“…An examination of essays written by depressed, formerly-depressed, and non-depressed college students at University of Texas [17] confirmed an elevated use of the word "I" in particular and also found more negative emotion words in the depressed group. Similarly, a Russian speech study [18] found a more frequent use of all pronouns and verbs in past tense among depression patients. A recent study based on English forum posts [19] observed an elevated use of absolutist words (e.g.…”
Section: Depression and Languagementioning
confidence: 79%